EVALUASI KEBIJAKAN PENGENDALIAN MUTU OBAT DENGAN UJI KETERSEDIAAN HAYATI = EVALUATION OF QUALITY ASSURANCE POLICY OF COPY DRUG ... - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2005)
Background: Quality assurance of copy drug is a part of national drug policy. It aims to protect people from substandard of copy drug quality. Instrument to ensure the copy drug have a good quality is bioequivalence testing. Government regulation on drug registration had been established since 1971 with regular update. Drug and Food agencies had developed the draft of bioequivelence testing on 2002, but this guidelines has not be an implemented yet. Department of Clinical Pharmacology of Gadjah Mada University is one of the independent institution of bioequivalence testing in Indonesia, since 1984. Objective: To evaluate the Indonesia draft gudelines of bioequivalence testing compare with the WHO bioequivalence guidelineâs and to evaluate bioequivalence testing that conducted by Department of Clinical Pharmacology Faculty of Medicine, Gadjah Mada University. Methods: Descripive analytic method used to compare the draft of Indonesia guidelines with WHO guidelineâs. A case study methods used to evaluate the bioequivalence testing in Department of Clinical Pharmacology Faculty of Medicine Gadjah Mada University. Results: The draft of Indonesia guidelines met with WHO guidelineâs. In the statistical analysis is more detail than WHO guideline. Department of Clinical pharmacology was adhare with WHO regulation on bioequivalence testing. Most of the copy drugs showed bioequivalence with their comparator and showed a good quality. All copy drug that tested in Dept. Clinical Pharmacology is before marketing evaluation. Conclusion: It is concluded therefore, Goverment has been developed the bioequivalence testing guideline that met with WHO guideline. Bioequivalence testing that is conducted in Department of Clinical Pharmacology met with WHO regulation. Keywords: policy evaluation, drug quality, copy/generic drug